Environmental Factors that Influence Culinary Creativity from the Perspectives of Turkish Cuisine Professionals - Özgönül, Sedef; Öztürk, Betül (Anais Brasileiros de Estudos Turísticos, 2022)
This study explores environmental factors that influence the culinary creativity of Turkish cuisine. Although Turkish food culture is known for its richness and diversity in terms of ingredients and cooking techniques, the assumption is that environmental factors cause some recognition and representation issues internationally. For this reason, a quantitative questionnaire study was carried and aimed to understand perceptions of chefs (hotel and restaurant chefs) and academicians (instructor chefs and academicians) towards factors that influence culinary creativity in Turkey. The exploratory factor analysis revealed six environmental factors that impact the culinary creativity of Turkish cuisine. These are (1) politics and economics, (2) education, (3) culture, (4) media and globalization, (5) technology, science, and design, (6) tourism. According to the study results, while the highest scores were given to educational factors by the participants, the media and globalization's impact was found to be the least concerned factors. The results demonstrate the significant differences are between participants' job specifications, genders, and education degrees. Moreover, this study suggests that cuisine is a designed phenomenon since it includes unique ingredients, cooking techniques and skills, flavors principles, and particular stakeholders. Thus, the proper management of these elements will provide cuisine a competitive advantage in the culinary industry. Chefs are the primary actors representing a cuisine in the international culinary industry and differentiate it from its competitors with their creative approaches.